Exploring bitcoin cross-blockchain interoperability: estimation through Hurst exponent - Nan, Zheng (Frontiers in Blockchain, 2024)
This study aims to investigate the interoperability of the Bitcoin blockchain by comparing the US dollar prices of five cryptocurrencies derived from the Bitcoin price with their corresponding market prices. The deviation rate between the derived price and the market price, referred to as the arbitrage return rate, is examined with respect to its adherence to the efficient market hypothesis and martingale theory principles, specifically regarding mean-reversion and serial independence. Hurst exponents are estimated using R/S and DFA methods, and their dynamics are analyzed using a sliding window technique. Our findings demonstrate that the Bitcoin blockchain effectively facilitates transactions among the five cryptocurrencies, though evidence suggests a potential structural change in Bitcoin blockchain interoperability following April 2023.